Nasal Sinus Tract of Odontogenic Origin: Report of a Case - Sagar Sareen; Anjani Kumar Pathak; Parth Purwar; Jaya Dixit; Divya Singhal; Isha Sajjanhar; Kopal Goel; Vaibhav Sheel Gupta (Case Reports in Dentistry)
Extraoral sinus tract often poses a diagnostic challenge to the clinician owing to its rare occurrence and absence of symptoms. The accurate diagnosis and comprehensive management are inevitable as the aetiology of such lesions is often masked and requires holistic approach. The present case report encompasses the management of an extraoral discharging sinus tract at the base of the right nostril in a chronic smoker. The lesion which was earlier diagnosed to be of nonodontogenic origin persisted even after erratic treatment modalities. Our investigations showed the aetiology of sinus tract to be odontogenic. Initially, a five-step program as recommended by the Agency for Health Care Research and Quality was used for smoking cessation followed by root canal therapy (RCT) and surgical management of the sinus tract. The patient has been under stringent follow-up and no reoccurrence has been noted.